RELATIONSHIP BETWEEN NURSE SUPPORTS AND FEARS OF HOSPITALIZED SCHOOL AGE CHILDREN IN PKU MUHAMMADIYAH HOSPITAL, YOGYAKARTA, INDONESIA - Istinengtiyas Tirta Suminar; Indria Laksmi Gamayanti; Lely Lusmilasari (Belitung Nursing Journal, 2017)
Background: Being hospitalized is usually related to the fear, especially for children. Nurse supports should be able to help the children to deal with the fears related to nurse and medical services. Objective: This study aims to examine the relationship between nurse support and the fear of school-age children being treated in the PKU Muhammadiyah hospital, Yogyakarta. Methods: This study employed a cross sectional correlation design, which was conducted from October to December 2016 in PKU Muhammadiyah Hospital, Indonesia. The samples of the study were 49 mothers and school-aged children who were admitted to the children ward. A consecutive sampling was applied to determine sample size. The instruments used in this study were nurse support and CMFS-R (Child Medical Fear Survey-Revised) questionnaires. Chi square test was performed with significance level p = 0.05 and level of trust = 95% for data analysis. Results: Findings showed 42.9% of respondents had medical fear and 36.7% of them had medical fear related-behavior responses. The nurse support was in a high category (73.5%). Chi square test showed p-value 0.038 (>0.05), which indicated that there was statistically no significant relationship between nurse support and children fear. There was only age of the children had a significant relationship with fear with p-value 0.035 (<0.05). Conclusions: There was no significant association between nurse support and fear of school-age children.